Factors that affect the English language teaching - learning process in Ecuadorian public high schools - Saltos Vivas, María Alexandra (2013)
This research is about “Factors that affect the English language teaching - learning process in Ecuadorian public high schools” and its purpose is to analyze the factors that affect the English language teaching-learning process. In addition, main variables studied were related to factors such as, teachers, students, classroom and educational institutions. This study was conducted in five public high schools in the city of Chone, province of Manabí. The sample consisted of 15 experienced English teachers and 15 students of different grades, ranging from 12 to 16 years old of age. The method applied in this study was a Quantitative and the techniques used in this research were surveys and note taking. Also, instruments such as observation formats and questionnaires were used for observing and interviewing teachers and students. The analysis of results showed that class size and classroom space affect the English teaching - learning process making the development and management of the class difficult due to the great number of learners in a small classroom with a single teacher conducting a large group of students.